Comparison of Antimicrobial Activity between Chemical Disinfectants on Contaminated Orthodontic Pliers - Carvalho, Maria Reggiani Azevedo (2015)
AIM: To compare the antimicrobial activity of the chemical substances--70% isopropyl alcohol, 2% glutaraldehyde (GTA) and 0.25% peracetic acid (PAA) in disinfecting orthodontic pliers contaminated in vitro with Streptococcui mutani, Staphylococci aureui and Candida albicani. MATERIALS AND METHODS: Distal end cutter pliers were divided into five groups: group 1 (negative control--sterilized pliers), group 2 (positive control--sterilized plier, subsequently contaminated), group 3 (disinfected with 70% isopropyl alcohol, friction method), group 4 (disinfected with 2% GTA, immersion method for 30 minutes), group 5 (disinfected with 0.25% peracetic acid (PAA), immersion method for 10 minutes). After the pliers were treated with one disinfectant and submitted to microbiological evaluation (by counting colony forming units), they were submitted to the same cleansing, sterilizing and contaminating processes, and were used in the following groups (crossover and washout study). The two-factor analysis of variance (ANOVA) test, followed by the Tukey test, was used to compare the groups. RESULTS: The results showed that there was no statistically significant difference between the three tested disinfectants. CONCLUSION: Although there were no statistically significant differences between the disinfectants, the chemical agents 2% glutaraldehyde and 0.25% PAA were effective in inhibiting the growth of the three microorganisms tested; however, 70% isopropyl alcohol was unable to completely eliminate S. aureui. CLINICAL SIGNIFICANCE: The chemical substances 2% glutaraldehyde and 0.25% PAA completely eliminated the microorganisms tested.